2m+3=11

Simple and best practice solution for 2m+3=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+3=11 equation:


Simplifying
2m + 3 = 11

Reorder the terms:
3 + 2m = 11

Solving
3 + 2m = 11

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2m = 11 + -3

Combine like terms: 3 + -3 = 0
0 + 2m = 11 + -3
2m = 11 + -3

Combine like terms: 11 + -3 = 8
2m = 8

Divide each side by '2'.
m = 4

Simplifying
m = 4

See similar equations:

| -40*(-24)= | | 6n+1=19 | | 10-25s= | | 10(20+10)= | | 2x-33=9-4x | | 66-3x=2x+6 | | 10x+10y= | | 10(x+y)= | | g-4=2g-7 | | 4(1-n)= | | -13.9*(-17.3)= | | 3(3x-4)=18 | | 4(2t-5)=36 | | 8y-12=5y | | 3y+-u+4u= | | 5-8x=31-15x | | 33-6x=3x+20 | | 4x+36=13x-72 | | 0=x^2+6x-5 | | -6(5-3x)=8x-7 | | m^2-4m-12=0 | | m^2-12=4m | | (16k)x(75k)= | | -5x+2=7x-4 | | 2/3=18 | | 3/4=12 | | 1/2+7=x-4 | | 1/2+7=x-4 | | 6=33-7x | | 3x-4=-6+11 | | 16x^2+14x-14=0 | | 16x^2+14x-16=0 |

Equations solver categories